2010
DOI: 10.1348/000709909x470483
|View full text |Cite
|
Sign up to set email alerts
|

Test selection, adaptation, and evaluation: A systematic approach to assess nutritional influences on child development in developing countries

Abstract: Background Evaluating the impact of nutrition interventions on developmental outcomes in developing countries can be challenging since most assessment tests have been produced in and for developed country settings. Such tests may not be valid measures of children's abilities when used in a new context. Aims We present several principles for the selection, adaptation, and evaluation of tests assessing the developmental outcomes of nutrition interventions in developing countries where standard assessment tests d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…Cross-cultural studies have shown biases in task performance based on different language structures (Jukes and Grigorenko, 2010), and different levels of stimulus familiarity (Callaghan et al, 2012; Zuilkowski et al, 2016). For example, in an attempt to address item bias when adapting a neuropsychological test used in Western cultures to be accessible for the Indonesian population, Prado et al (2010) changed a picture stimulus of a “bunny” to a “chicken.” However, despite these modifications, young children were still unable to complete the assessment successfully (Abubakar et al, 2008). This may have resulted from other age or language related biases that may have restricted children's participation, in that children might not have understood the task in hand.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-cultural studies have shown biases in task performance based on different language structures (Jukes and Grigorenko, 2010), and different levels of stimulus familiarity (Callaghan et al, 2012; Zuilkowski et al, 2016). For example, in an attempt to address item bias when adapting a neuropsychological test used in Western cultures to be accessible for the Indonesian population, Prado et al (2010) changed a picture stimulus of a “bunny” to a “chicken.” However, despite these modifications, young children were still unable to complete the assessment successfully (Abubakar et al, 2008). This may have resulted from other age or language related biases that may have restricted children's participation, in that children might not have understood the task in hand.…”
Section: Introductionmentioning
confidence: 99%
“…Its study therefore has become in recent years an essential part of studies of child development outcomes following exposures and interventions in the prenatal period and infancy (A. Abubakar, Van Baar, Prado et al, 2010;Stoltzfus et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other papers (this volume) (Baddeley, Gardner, & Grantham-McGregor, 1995;Greenfield, 1997;Holding et al, 2004;Prado, et al, 2010) have highlighted the dangers of insufficiently adapted or culturally inappropriate test instruments when examining non-verbal cognitive development. These dangers are even greater in the field of language development since the task that children have in learning their native language is radically different depending on the language itself.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, correlation, regression and factor analysis methods are applied to reject an inefficient test. The first two methods allow estimating the so-called statistical pure contribution of each task to the general variation of test scores, while the factor analysis is a good method for checking the homogeneity of the test (Bortz & Döring, 2005;Avanessov, 2009;Prado et al, 2010;Lim & Chapman, 2013). As a result, these methods indicate suitability, or unfitness of the considered test (Boesen & Palm, 2010;Xia, Liang & Wu, 2017).…”
Section: Methods and Datamentioning
confidence: 99%